The King Arthur case - Bannalec, Jean-Luc, 1966- (Bannalec, Jean-Luc, 1966- Commissioner Dupin, 2022)
"The King Arthur Case is the seventh installment of Jean-Luc Bannalec's bestselling mystery series. The forest of Broceliande, with its picturesque lakes and castles, is the last remnant of the fairy kingdom, if Breton lore is to be believed. Innumerable legends spanning thousands of years are set here, including the tale of King Arthur and the Round Table. It seems to be an appropriate destination for Commissaire Dupin and his team to take a late summer field trip. But when the body of a historian turns up, Dupin is called upon to investigate in the brutal murder case. Before too long, there are more victims. What knowledge do the assembled scientists have about the most recent archaeological digs in the area? Where do they stand on the controversial decision to turn parts of the forest into an amusement park? And why is no one willing to talk? Even Nolwenn, Dupin's unshakeable assistant, is concerned. And that means trouble. Mysterious, ingenious, and suspenseful: Dupin's seventh case takes him and his team into the very heart of Brittany"--